Modified Prostate Health Index Density Significantly Improves Clinically Significant Prostate Cancer (csPCa) Detection - Chen, Haojie; Qian, Yuhang; Wu, Yanyuan; Shi, Bowen; Zhou, Jiatong; Qu, Fajun; Gu, Zhengqin; Ding, Jie; Yu, Yongjiang (Frontiers in Oncology, 2022)
Background Early screening of clinically significant prostate cancer (csPCa) may offer opportunities in revolutionizing the survival benefits of this lethal disease. We sought to introduce a modified prostate health index density (mPHI) model using imaging indicators and to compare its diagnostic performance for early detection of occult onset csPCa within prostate specific antigen (PSA) grey zone with that of PHI and PHID. Methods and Participation Between August 2020 and January 2022, a training cohort of 278 patients (total PSA 4.0 - 10.0 ng/mL) who were scheduled for a prostate biopsy was prospectively recruited. PHI and PHID were compared with mPHI (LD/(TRD×APD×TPV) ×PHI) for the diagnosis performance in identifying csPCa. Pathology outcomes from systematic prostate biopsies were considered the gold standard. Results This model was tested in a training cohort consisting of 73 csPCa, 14 non-clinically significant prostate cancer(non-csPCa), and 191 benign prostatic hyperplasia (BPH) samples. In the univariate analysis for the PSA grey zone cohort, for overall PCa, the AUC of mPHI (0.856) was higher than PHI (0.774) and PHID (0.835). For csPCa, the AUC of mPHI (0.859) also surpassed PHI (0.787) and PHID (0.825). For detection of csPCa, compared with lower specificities from PHI and PHID, mPHI performed the highest specificity (76.5%), by sparing 60.0% of unnecessary biopsies at the cost of missing 11 cases of csPCa. The mPHI outperformed than PHI and PHID for overall PCa detection. Considering csPCa, mPHI has a exceed diagnostic performance with a better net benefit in decision curve analysis (DCA) compared with PHI or PHID. Conclusions We have developed a modified PHI density (mPHI) model which can sensitively distinguish early-stage csPCa patients within the PSA grey zone.